2006
DOI: 10.1007/s10194-006-0312-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific features of migraine syndrome in children

Abstract: The aim of the study was to define factors that can be used to distinguish migraine headaches from primary non-migraine headaches. Specific characteristics of headaches were analysed in 30 636 children aged 3–17; 18.97% had recurrent primary non-migraine headaches, whereas 8.63% had migraine headaches. Migraine attacks follow identical patterns (94.9%): occurring monthly (78.0%), occurring in morning hours (58.5%), lasting for several hours (45.1%) and ending after sleep (76.7%). Nausea, vomiting impulse and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…usually start in the morning hours (58.5%) and resolve after a period of sleep (76.7%). The most specific features separating migraines from tension-type headache are improvement after sleeping, the presence of nausea and vomiting, worsening with physical activity and photo-, phono-or osmophobia (5).…”
mentioning
confidence: 99%
“…usually start in the morning hours (58.5%) and resolve after a period of sleep (76.7%). The most specific features separating migraines from tension-type headache are improvement after sleeping, the presence of nausea and vomiting, worsening with physical activity and photo-, phono-or osmophobia (5).…”
mentioning
confidence: 99%
“…RH appear with higher frequency in the second-born child (1: 1.73, compared with the first-born one), but without significant difference when compared with other children in a family [22] . 37% of the children observed were from families with 2 children, and only 4.5% of them came from families with 3 or more children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distribution could reflect some concern among primary care medical doctors of a link with serious diseases of the central nervous system. Nonspecific medication given more than twice per week was noted in 13.5% of children with RH, being 7 times more frequently used in children with nonmigraine than in children with migraine headache [22] . Brna et al [23] found that nonprescribed medications were used by 70% of those with ongoing headaches, while prescribed medications were used by 14% of persons with headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations